(untitled) (Research, Society and Development, 2022)
The aim of the present study was to review the effect of interval training on weight loss in adults. A search was made for the materials through Google Scholar, based on articles published between January 2011 and December 2020. Six researchers make up this review and the following information is addressed in them: interval training protocols, HIIT, interval training efficiency, advantages of interval training, physiological adaptations from interval training, predominant energy pathways in interval training, interval training and weight loss, intermittent exercises, interval exercises and VO2max. Two studies do not define interval training as influential in weight loss, while four points out the relationship between volume and intensity of the methodology studied, great influence on general physical changes and focus on weight loss. Even considering this direct relationship, the proposed intensity is responsible for the quality and quantity of the result sought.